Iron profile in Thoroughbreds during a standard training program. Issue 3 (March 2016) - Assenza, A; Casella, S; Giannetto, C; Fazio, F; Tosto, F; Piccione, G
Abstract : Objectives: The aim of this study was to evaluate the modifications of some haematological parameters and iron profile during an 80‐day training program and their relationship with athletic performance of performance horses. Methods: During the training period, 20 Thoroughbreds were subjected to a standardised exercise test, previously standardised for gallopers to evaluate athletic performance. The test was performed immediately before the beginning of the training program (T0) and after 30 days (T30), 60 days (T60) and 90 days (T90). For each horse, their velocities at blood lactate concentrations of 2 and 4 mmol/L (V2 and V4) and a heart rate of 200 beats/min (V200) were calculated to assess the effect of the training program on athletic performance. Blood samples were collected at 20‐day intervals over a period of 80 days from the beginning of the training program. Results: One‐way repeated measures analysis of variance (ANOVA) showed a statistically significant effect of days of training (time) on iron, ferritin, transferrin, total iron‐binding capacity, transferrin saturation and unsaturated iron‐binding capacity (P < 0.001 for all). Conclusions: The results showed the influence of the intensity and duration of exercise on iron metabolism. These findings may be useful for evaluating the athletic status of horses during training and to assess the degree of training adaptability, providing an opportunity to modify the training schedule to achieve the desired performance.